Biometrical relationship of ovaries and pituitary during prepubertal period in goat (Capra hircus) - NAGAMALLESWARI, Y; IYYANGAR, M P; GOPINATH, S; RAGHAVENDER, K B P (The Indian Journal of Animal Sciences, 2014)
Ovaries and pituitary glands from 50 healthy non-descriptive female goats of day-old to 12-month-old were studied. The present investigation revealed an increasing tendency in the biometrical values of pituitary and ovaries in respect of length, width, weight and thickness with the advancement of age. The overall mean values of right ovaries in respect of above parameters were significantly higher (P<0.05) than the left ovaries between the groups and within.